Cumulative Energy Demand and Greenhouse Gas Emissions from Potato and Tomato Production in Southeast Brazil - Breno de Jesus Pereira; Newton La Scala; Arthur Bernardes Cecílio Filho (Agronomy)
Knowing the energy balance in agricultural systems is essential for a holistic understanding of sustainability, productivity and economic return. The aim of this study was to estimate the cumulative energy demand (CED), greenhouse gas (GHG) emissions and carbon footprint in industrial potato and tomato production systems in the Southeast region of Brazil, identifying mitigation strategies in different scenarios. The Life Cycle Analysis methodology was used, and two functional units were defined: one hectare of cultivation and one kilogram of vegetable produced. The CEDs for tomato and potato production were 59,553.56 MJ ha–1 (or 0.54 MJ kg–1) and 57,992.02 MJ ha–1 (or 1.45 MJ kg–1), respectively. The GHG emissions were 5425.13 kg CO2 eq ha–1 for potato production and 5270.9 kg CO2 eq ha–1 for tomato production, resulting in carbon footprints of 0.135 and 0.042 kg CO2 eq kg–1, respectively. Fertilizers, diesel and pesticides were the main contributors to CED and GHG emissions. Thus, in order to achieve greater sustainability in the production of these vegetables and mitigate the impacts on the environment generated by the high demand for energy and GHG emissions, it is necessary to replace synthetic fertilizers with organic sources, chemical pesticides with biological pesticides, diesel with biodiesel or the use of electric vehicles and tractors, resulting in reductions of up to 39 and 52% in the GHG emissions for potatoes and tomatoes, respectively.